Witnessing trauma through discordant chronology of words in Yvonne Vera's Under the Tongue - Dodhy, Shamaila; Jujar Singh, Hardev Kaur (Penerbit Universiti Sains Malaysia, 2018)
Yvonne Vera is a reformist writer of Zimbabwe who agitated the society to attend to serious issues in the life of a Zimbabwean woman. This paper will examine Yvonne Vera’s Under the Tongue in which representations of language of monologue contribute to the creation of an atmosphere in which the pain of female body is obviously felt. The legacies of colonialism and strategic policies of nationalism collaborate to facilitate the vulnerability of women thus contributing to their violation of rights and victimisation. It is a metaphorical representation of female resistance against violent male Zimbabwean society. The trauma of the victim is thoughtfully integrated into linguistic and symbolic systems aesthetically created by the writer. Using the discordant chronology of words of the female protagonist, Vera stylistically identifies the silence of a girl who is captive of flashbacks and intrusive thoughts but struggles to liberate herself from the discourse of pain. Restoration of confidence does take place with the power of language. By articulating a private experience of a victimised young girl, the writer reclaims the essential power of women’s speech and silences in the context of gendered nationalist ideology where sacrifices of women have been reduced to an invisible state by historiographers.